Efforts to Reduce Non-Technical Losses by Maintaining Kwh Meters at PT. PLN (PERSERO) ULP Panarukan - Diana Pratiwi; Zuraidah Tharo; Dino Erivianto (SEAN Institute, 2026)
This study aims to analyze the effectiveness of kWh meter maintenance as an effort to reduce non-technical losses in the electricity distribution system at PT. PLN (Persero) ULP Panarukan. Non-technical losses, which are often caused by meter inaccuracy, recording errors, and illegal usage, have a direct impact on the company's revenue. Using a quantitative descriptive approach, this study compares the level of non-technical losses before and after the implementation of a structured kWh meter maintenance and replacement program. Data were collected through field observations, interviews, and documentation from PLN's internal systems (ACMT, AP2T, EIS). The results show that maintenance activities successfully improved measurement accuracy, which led to a decrease in unrecorded energy. Thus, non-technical losses were reduced and resulted in significant financial savings. In addition, the study proposes an age-based meter replacement Operational Target (TO) as a strategic framework for determining maintenance action priorities. It is concluded that optimizing the maintenance program for aging kWh meters is a crucial operational step in controlling non-technical losses and securing PT. PLN's revenue.